Mesenchymal stromal cells-exosomes: a promising cell-free therapeutic tool for wound healing and cutaneous regeneration. Issue 1 (26th December 2019) - Hu, Peng; Yang, Qinxin; Wang, Qi; Shi, Chenshuo; Wang, Dali; Armato, Ubaldo; Prà, Ilaria Dal; Chiarini, Anna
Abstact: Cutaneous regeneration at the wound site involves several intricate and dynamic processes which require a series of coordinated interactions implicating various cell types, growth factors, extracellular matrix (ECM), nerves, and blood vessels. Mesenchymal stromal cells (MSCs) take part in all the skin wound healing stages playing active and beneficial roles in animal models and humans. Exosomes, which are among the key products MSCs release, mimic the effects of parental MSCs. They can shuttle various effector proteins, messenger RNA (mRNA) and microRNAs (miRNAs) to modulate the activity of recipient cells, playing important roles in wound healing. Moreover, using exosomes avoids many risks associated with cell transplantation. Therefore, as a novel type of cell-free therapy, MSC-exosome -mediated administration may be safer and more efficient than whole cell. In this review, we provide a comprehensive understanding of the latest studies and observations on the role of MSC-exosome therapy in wound healing and cutaneous regeneration. In addition, we address the hypothesis of MSCs microenvironment extracellular vesicles (MSCs-MEVs) or MSCs microenvironment exosomes (MSCs-MExos) that need to take stock of and solved urgently in the related research about MSC-exosomes therapeutic applications. This review can inspire investigators to explore new research directions of MSC-exosome therapy in cutaneous repair and regeneration.